Modelling of plasma motion response induced by an external rotating helical perturbation in the HYBTOK-II tokamak - Pankratov, I.M.; Omelchenko, A.Ya.; Olshansky, V.V. (Вопросы атомной науки и техники, 2005)
In addition to the analysis of magnetic perturbation amplitudes [2] a detailed investigation of the plasma motion affected by this external helical magnetic perturbation is carried out near the HYBTOK-II main resonance surface.